Impact of COVID-19 on unorganized Indian retail markets - Amgad S.D. Khaled; Khaled Ismail Alshaketheep; Mosab I. Tabash; Mohammad Azmi Khan; Mohammad Ahmad Al-Omari (Innovative Marketing)
As informal workers struggle to survive the current crisis, there is reason to believe that more strain would also be exerted on the already fragile sector in the post-crisis era. The implications of the COVID-19 outbreak for the informal economy will continue. Faced with a long crisis, the global economy would likely shrink demand for informal goods and services. The primary goal of this paper is to study consumer behavior during the pandemic, investigate government-implemented Standard Operating Procedures (SOPs) for the unorganized retail sector, and determine if consumers prefer to have goods delivered to their homes rather than visit retail stores. This paper collected information from a number of Indian customers who made unorganized retail transactions in New Delhi and NCR Region. The sample was taken from 700 citizens of New Delhi, India. The study found that product variety, digital payment, scheduling, free delivery and lower speed have a significant effect on customer behavior. In addition, SOPs do not influence consumer behavior. The main reasons for choosing a specific channel are simple availability, security, less hassle, and compliance with all laws. The pandemic led to a renewed trust in the local Kirana shop, with new clients visiting metro and non-metro shops locally. The system in Kirana has changed from physical sales to digital aviation because of the pandemic.